Influence of space charged particles on satellite optical communication system - Hou, Rui; Zhao, Shanghong; Xu, Jie; Wu, Jili; Li, Yongjun; Zhan, Shengbao; Shi, Lei; Fang, Shaoqiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Although research of satellite optical communication system has been carried out for many years, there is scarce literature to comprehensively analyze the influence of space environment on satellite optical communication system. Different kinds of particles and fields exist in the space environment, including high energy charged particles, solar radiation, plasma environment, space fragment, etc. The Influence of space charged particles on satellite optical communication system was investigated in detail, which mainly related to single event upset (SEU), total dose effect and plasma environment. For SEU analysis the relation between single proton upset rate and satellite orbit was analyzed in detail. The reliability index of equipment based on SEU was proposed, the numerical calculation results have proved that the SEU effect was relatively less and corresponded to higher reliability of SRAM/MOS equipment under lower orbit altitude and inclination. For plasma environment analysis there is no obvious influence of plasma on laser signal transmission. But charging and discharging processes on satellite surface would lead to the malfunction of satellite communication system. The influence of charged particles and its related plasma on satellite optical communication system was investigated, which would be helpful for the design and the improvement of performance of satellite optical communication system.
Optica Applicata, Vol. 39, 2009, nr 2, s. 251-265
Keywords: optyka; satellite optical communication; charged particle; single event upset; plasma